Response of Information Technology Companies in Europe to the World Health Organization's Announcement of the COVID-19 Pandemic - Katerina Lyroudi; Fatbardha Morina; Chrysanthi Balomenou (ENTRENOVA - ENTerprise REsearch InNOVAtion, 2021)
From the beginning of 2020, the whole world has been shaken by a contagious disease called Covid-19, its actual name being SARS-CoV-2. It first appeared in China, in Wuhan, Hubei Province, in December 2019, and the World Health Organization (WHO) was informed about it on the 31st of December 2019. On the 11th of March, 2020, WHO declared the Covid-19 outbreak a pandemic, and no country has been able to contain this coronavirus. This medical or health crisis evolved into a pandemic and led to a global economic crisis. This study investigates the wealth effect of the coronavirus pandemic announcement on the Information Technology Industry companies in Europe. We apply the classical event study methodology. Our sample contained 87 companies. The results show a strong negative reaction of information technology companies upon this announcement. The European investors perceived this announcement as a negative signal that will disturb the lives of everyone and will create economic instabilities and havoc in all sectors of an economy.
Keywords: G14; G30; 330; market reaction; event study; Covid-19 crisis